Perlaksanaan Konsep Komuniti Berpagar: Kajian Kes di USJ, Subang Jaya, Selangor - Ahmad Farid, Mohammed (2011)
Housing project with the concept of gated communities has become the latest trend in the property sector, especially in Selangor. In fact, many areas are at the beginning of construction does not use the concept of gated communities also implement such an ad-hoc basis. This is because people want their peaceful residential area and free from the threat of criminals. Lately a lot of crime occurred in residential areas to raise concerns of local residents. Some areas are trying to implement a voluntary patrol scheme, but failed to achieve its goals and finally had to hire security guards to protect their safety. They felt that the steps to create the GC is intended to assist the authorities in the prevention of crime. The purpose of this study is to determine the fear of crime amongs the residents, reason for staying in areas of research, understanding of the guidelines and also the problems faced by people when implementing the concept of gated communities. The author focuses on issues involving the study of the safety and guidelines for an offense that is always done when implementing the GC has to do with guidelines such as closing the road, asking for ID and the issue of high costs of security fees. This study is conducted via a qualitative study of two areas of USJ 11 / 3 and USJ 16, Subang Jaya. Interviews conducted with seven respondents to seek input. This study found that gated communities can help the authorities in preventing crime and reducing crime. In addition, results from residents activities in crime prevention has established close ties among the local people hence dismissed the notion that people in the gated community to be individualistic and only suitable for implementation in the elite class.